Innovative, complementary and alternative therapy in inflammatory bowel diseases: A broad 2020s update - Masi, Letizia; Ciuffini, Cristina; Petito, Valentina; Pisani, Laura Francesca; Lopetuso, Loris Riccardo; Graziani, Cristina; Pugliese, Daniela; Laterza, Lucrezia; Puca, Pierluigi; Di Vincenzo, Federica; Pizzoferrato, Marco; Napolitano, Daniele; et al. (Frontiers in Gastroenterology, 2022)
Inflammatory bowel diseases (IBD) are chronic disabling conditions with a complex and multifactorial etiology, which is still not completely understood. In the last 20 years, anti-TNF-α antagonists have revolutionized the treatment of IBD, but many patients still do not respond or experience adverse events. Therefore, new biological therapies and small molecules, targeting several different pathways of gut inflammation, have been developed of which some have already been introduced in clinical practice while many others are currently investigated. Moreover, therapeutic procedures such as leukocytapheresis, fecal microbiota transplant and stem cell transplantation are currently being investigated for treating IBD. Lastly, complementary and alternative medicine has become a field of interest for gastroenterologist to reduce symptom burden in IBD patients. In this comprehensive and updated review, a novel classification of current and developing drugs is provided.